Identifikasi Keterlambatan Pengiriman Produk Departemen Produksi Extrussion Blow Molding Di PT X Surabaya - Alvenia Oktapia; Felecia Felecia (Jurnal Titra, 2018)
In 2017 PT X Surabaya got a delay problem up to 49 times in Extrussion Blow Molding (EBM) department, therefore a research was conducted to identify causes of the delay. This research used quantitative approach by using one of seven basic tools, which is Cause and effect diagram as a tool for analyzing the cause of the delay. Data that used in this research is the internal data from PT X Surabaya, which are Daily Production Report of 2017 and 2018 (January – March), COOIS data of 2017, resume CS data of 2017, and latest Routing data of 2018. PT X Surabaya especially the production of EBM has four types of wasting time, they are waste waiting, waste waiting, waste excess processing, and waste defect. The result of this research is there are several causes of the delay that has percentage of contribution in PT X Surabaya which are Downtime (15.8%) that caused by worn out machine breaker, overheated machine temperature, color of product got mixed with other colors of old material, change of machine setting, tools crashed the mold continuously, and replacement tools not available. Speed gap (8.9%) caused by the hot room temperature, untighten clamping, worn out machine breaker, machine’s high temperature, and unbalanced machine carriage. Reject (4.9%) caused by the unclosed machine hooper, uncleaned machine barrel, overheated machine temperature, and mixer machine used to mix materials was dirty.